S100A9 Derived From Myeloma Associated Myeloid Cells Promotes TNFSF13B/TNFRSF13B-Dependent Proliferation and Survival of Myeloma Cells - Meng, Lingzhang; Tang, Qiang; Zhao, Jingjie; Wang, Zechen; Wei, Liuzhi; Wei, Qiuju; Yin, Lianfei; Luo, Shiguan; Song, Jian (Frontiers in Oncology, 2021)
Multiple myeloma (MM) is a lethal haematological malignancy characterized by abundant myeloid cells in the microenvironment that fuels tumor progression. But the mechanism by which myeloid cells support myeloma cells has not been fully explored. We aimed to examine their effect on bone marrow cells of MM patients by scRNA-seq transcriptome analysis and reveal a high-resolution gene profile of myeloma cells and myeloma associated myeloid cells. Based on correlation analysis of integrated scRNA-seq and bulk RNA-seq datasets from patients, we confirmed that myeloid-derived S100A9 was involved in TNFSF13B-dependent myeloma cell proliferation and survival. In the animal experiments, S100A9 was found to be critical for MM cell proliferation and survival via TNFSF13B production by myeloid cells, neutrophils, and macrophages. In-vitro analysis of patient primary myeloma cells further demonstrated that enhanced TNFSF13B signaling triggered the canonical NF-κB pathway to boost tumor cell proliferation. All these results suggest that myeloid-derived S100A9 is required for TNFSF13B/TNFRSF13B-dependent cell-fate specification, which provides fresh insights into MM progression.